Amtrak, America's railroad : transportation's orphan and its struggle for survival - Doughty, Geoffrey H.; Darbee, Jeffrey T.; Harmon, Eugene E. (Railroads past and present, 2021)
"Discover the story of Amtrak, America's Railroad, 50 years in the making. In 1971, in an effort to rescue essential freight railroads, the US government founded Amtrak. In the post-World War II era, aviation and highway development had become the focus of government policy in America. As rail passenger services declined in number and in quality, they were simultaneously driving many railroads toward bankruptcy. Amtrak was intended to be the solution. In Amtrak, America's Railroad: Transportation's Orphan and Its Struggle for Survival, Geoffrey H. Doughty, Jeffrey T. Darbee, and Eugene E. Harmon explores the fascinating history of this beloved institution and tell a tale of a company hindered by its flawed origin and unequal quality of leadership, subjected to political gamesmanship and favoritism, and mired in a perpetual philosophical debate about whether it is a business or a public service. Featuring interviews with former Amtrak presidents, the authors explore the current problems and issues facing Amtrak and their proposed solutions. Created in the absence of a comprehensive national transportation policy, Amtrak manages to survive despite inherent flaws due to the public's persistent loyalty. Amtrak, America's Railroad is essential reading for those who hope to see another fifty years of America's beloved railroad passenger service"--